2000
DOI: 10.1002/1531-8257(200003)15:2<230::aid-mds1005>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced Parkinson's disease by unilateral posterior GPi pallidotomy: 4-year results of a pilot study

Abstract: To assess the long‐term outcome following unilateral pallidotomy for advanced Parkinson's disease, we performed nonblinded Core Assessment Program for Intracerebral Transplantations protocol assessments in 10 of the original 15 patients in our pilot study for 4 years following surgery. Although Unified Parkinson's Disease Rating Scale motor examination scores returned to baseline levels at 3 and 4 years, most patients continued to show sustained improvements in contralateral tremor, akinesia, and drug‐induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 22 publications
1
60
0
4
Order By: Relevance
“…These results are in accordance with two other reports on the long-term effects of UPVP. In the study by Baron et al, improvement in contralateral tremor, akinesia and drug-induced dyskinesias was present four years after surgery in a group of 10 out of the 15 initial patients [3]. Fine et al showed sustained effects on contralateral parkinsonian signs and dyskinesias in 17 patients evaluated at two-year follow-up, with some patients also being assessed at a longer follow-up period up to 64 months [8].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results are in accordance with two other reports on the long-term effects of UPVP. In the study by Baron et al, improvement in contralateral tremor, akinesia and drug-induced dyskinesias was present four years after surgery in a group of 10 out of the 15 initial patients [3]. Fine et al showed sustained effects on contralateral parkinsonian signs and dyskinesias in 17 patients evaluated at two-year follow-up, with some patients also being assessed at a longer follow-up period up to 64 months [8].…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have presented their results at longer follow-up periods of two [14,16] and three years [24] but there are only three studies [3,7,8], involving only small numbers of pas Abstract Background Pallidotomy is widely accepted as a treatment for patients with Parkinson's disease (PD) who have disabling symptoms that are inadequately controlled with pharmacotherapy. There are, however, only a few studies, with a small number of patients, showing evidence after prolonged periods of time about the clinical outcome after pallidotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report reductions in anxiety and depression after pallidotomy that are unrelated to the improved motor function [76,78,136,137]. Short-(6 month) and long-term (4 years) follow-up in a carefully evaluated series suggested that pallidotomy has no consistent effects on depression or anxiety, but that a history of a previous or active affective disturbance at the time of surgery may be most closely associated with subsequent development of a mood disorder [12,138].…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…Increased and abnormally patterned output in motor-related circuits of the basal ganglia to the thalamus may in part be responsible for the motor disturbances in Parkinson's disease (PD) (Albin et al, 1989;Bergman et al, 1990;DeLong, 1990;Wichmann and DeLong, 1996). Based on this premise and from previous experiences with pallidal ablative surgeries in patients with PD (Talairach et al, 1950;Guiot and Brion, 1953;Riechert and Wolff, 1953;Narabayashi and Okuma, 1954;Cooper and Bravo, 1958;Svennilson et al, 1960), the last decade has seen major advances in ablative and chronic stimulation techniques aimed at reducing basal ganglia output through interruption of neuronal activity in the internal pallidum (GPi) or the subthalamic nucleus (STN) (Laitinen et al, 1992;Benabid et al, 1994;Lozano et al, 1995;Krack et al, 1998;Baron et al, 1996Baron et al, , 2000Alvarez et al, 1999Alvarez et al, , 2000Fine et al 2000). Although the mechanisms by which electrical stimulation works in parkinsonian patients remain uncertain, the similarities between the effects of chronic stimulation and ablative lesions suggest that electrical stimulation may also serve to functionally inhibit the targeted nuclei.…”
mentioning
confidence: 98%